Childbirth preparation and its facilitating and inhibiting factors from the perspectives of pregnant and postpartum women in Tabriz-Iran: a qualitative study - Zohreh Alizadeh-Dibazari; Fatemeh Abbasalizadeh; Sakineh Mohammad-Al; Shayesteh Jahanfar; Mojgan Mirghafourvand (BMC, 2024)
Abstract Background The World Health Organization recognizes childbirth preparation as an essential component of antenatal care, as it plays a crucial role in reducing maternal mortality and improving women's childbirth experience. Countries worldwide have implemented various interventions to assist women in preparing for childbirth, based on their own resources. This study was conducted with the aim of exploring the perspectives of pregnant and postpartum women on childbirth preparation and the facilitating and inhibiting factors, in Tabriz, Iran. Methods This qualitative study was conducted with 25 participants, selected purposively among pregnant women in weeks 37 to 40 of gestation and postpartum women within 10 days to 6 weeks after childbirth. Data collection was done through semi-structured, in-depth individual interviews using an interview guide. The data was analyzed using content analysis method with conventional approach. Results The perspectives of pregnant and postpartum women regarding childbirth preparation revealed that factors such as maternal health during pregnancy, having an antenatal care plan, improving health literacy, and developing a birth plan were identified as crucial elements for effective childbirth preparation. Additionally, mental and emotional preparation, support, financial planning, participation in preparation classes, and awareness of childbirth methods were recognized as facilitators. On the other hand, insufficient mental and emotional preparedness, inadequate support, weak antenatal care, information deficiencies, insufficient physical activity, and a lack of a birth plan were identified as barriers. Conclusion The findings highlight the multifaceted nature of childbirth preparedness, necessitating the involvement of families, the healthcare system, and the entire community. Utilizing the study results in strategic planning for pre-pregnancy, during pregnancy, and inter-pregnancy care can enhance childbirth preparedness and contribute to achieving Iran's population rejuvenation policy goals.